(untitled) (Revista Lusófona de Educação, 2018)
The potential of videogames in learning has been increasingly studied, documented and sustained. The present study aims to summarize quantitative results from digital Game-Based Learning (GBL) strategies, through a Systematic Review of Literature with Meta-analysis study, framing conclusions about the effectiveness of the use of videogames as a learning strategy in several contexts. Through a systematic search in scientific databases and researchers’ social networks (Ebsco, ACM, PubMed and ResearchGate), 68 papers were obtained. A screening process, based on inclusion criteria, such as the use of Randomized Controlled Trials (RCTs), digital GBL strategies and measures to evaluate concrete learning gains, resulted in a final sample of 14 experimental studies. Data was gathered and analyzed using two different matrices, and softwares (SPSS and CMA). Considering a joint sample of 1685 subjects, it is possible to mention that digital GBL strategies have shown larger effect-sizes than traditional approaches, namely expository, allowing larger and more effective learning outcomes. This study arises in the context of GamiLearning project, an action-research project, aiming to develop critical and participatory dimensions of media literacy in young people, from 9 to 12 years, through collaborative learning experiences with digital games. Keywords: meta-analysis; videogame-based learning; learning; education.